Dynamic Load Balancing with the Parallel Partitioning Tool GridSpiderPar - Golovchenko, E. N. (Mathematical models and computer simulations, 2022)
Dynamic adaptive meshes are often used in high-performance computing. A mesh is locally refined or derefined in spots of interest or where high gradients of an objective function arise. To balance the load of processors, it is required to periodically repartition it. Dynamic load balancing algorithms are developed based on the parallel geometric algorithm of mesh partitioning and the parallel incremental algorithm of graph partitioning using the partitioning tool GridSpiderPar. The initial partition of a mesh with a local refinement (6.7 × 10 6 hexahedrons) is compared with the results of repartitioning using the devised algorithms. A comparison of the results shows the advantages of the parallel geometric algorithm on this mesh and the features of using the parallel incremental algorithm.